Convergence of distinct functional networks supporting naming and semantic recognition in the left inferior frontal gyrus - Xu, Zhansheng; Shen, Bo; Taji, Wael; Sun, Pei; Naya, Yuji (Human brain mapping, 2020)
Naming individual objects is accompanied with semantic recognition. Previous studies examined brain‐networks responsible for these operations individually. However, it remains unclear how these brain‐networks are related. To address this problem, we examined the brain‐networks during a novel object‐naming task, requiring participants to name animals in photographs at a specific‐level (e.g., “pigeon”). When the participants could not remember specific names, they answered basic names (e.g., “bird”). After fMRI scanning during the object‐naming task, the participants rated familiarity of the animals based on their sense of knowing. Since participants tend to remember specific names for familiar objects compared with unfamiliar objects, a typical issue in an object‐naming task is an internal covariance between the naming and familiarity levels. We removed this confounding factor by adjusting the familiarity/naming level of stimuli, and demonstrated distinct brain regions related to the two operations. Among them, the left inferior frontal gyrus triangularis (IFGtri) contained object‐naming and semantic‐recognition related areas in its anterior‐ventral and posterior‐dorsal parts, respectively. Psychophysiological interaction analyses suggested that both parts show connectivity with the brain regions related to object‐naming. By examining the connectivity under control tasks requiring nonlexical semantic retrieval (e.g., animal's body color), we found that both IFGtri parts altered their targeting brain areas according to the required memory attributes, while only the posterior‐dorsal part connected the brain regions related to semantic recognition. Together, the semantic recognition may be processed by distinct brain network from those for voluntary semantic retrievals including object‐naming although all these networks are mediated by the posterior‐dorsal IFGtri.